Selected Financial Factors To Assessing The Wealth Of Local Government Units On The Example Of Rural And Ur-ban-Rural Communities In Zachodniopomorskie Voivodeship (Research Bulletins of the Faculty of Economic Sciences, 2017)
The main aim of this article is an attempt to identify the factors influencing the financial assessment of the wealth of communities. In the article the following issues were discussed: the essence of wealth in relation to local government units, the most important financial factors for this evaluation. The following methods were used: analysis of the literature, analysis of budget and debt indicators (including current income, income from taxes and charges, operating profit and debt service costs) and methods of descriptive statistics. The analysis includes financial data of rural and urban – rural communities in Zachodniopomorskie voivodeship in years 2010-2015. The analysis allowed for positive verification of the hypothesis according to which operating profit and the cost of debt service determine the level of affluence of communities.
Keywords: taxes and charges; operating profit; debt servicing; wealth